Sosialisasi Pengelolaan Keuangan Keluarga Melalui Investasi Syariah Pada Yayasan Daarut Tauhiid di Tangerang Selatan - Maulana, Reza (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This community service project aims to highlight the critical importance of effective family financial management, particularly within the context of Islamic principles among Indonesian Muslim families. Conducted at Yayasan Daarut Tauhiid, South Tangerang. Proper financial management in the family is essential because it ensures the well-being of the household, prepares for unexpected events, and enables investments that align with religious and ethical values. The program emphasized smart investment strategies by guiding participants to choose the most suitable Sharia-compliant financial products and prioritize long-term benefits over short-term gains. Topics covered included budgeting for essential needs, the importance of saving and establishing emergency funds, and selecting reliable halal investment instruments such as Islamic mutual funds, sukuk, and gold. Interactive seminars, discussions, and practical simulations were employed to ensure participants understood the nuances of making informed financial decisions. Results demonstrated a significant increase in participants' awareness of how proper financial management supports family well-being while adhering to Sharia guidelines, differentiating between conventional and Islamic financial products. This community service project underscores the necessity of financial literacy and education to cultivate sustainable family financial stability according to Islamic principles, contributing to both economic security and moral integrity.Keywords: Islamic Finance, Family Financial Management, Smart Investment, Sharia Investment, Halal Investment, Financial Literacy